The Mexican consensus on the diagnosis and treatment of diverticular disease of the colon - R. Raña-Garibay; N. Salgado-Nesme; R. Carmona-Sánchez; J.M. Remes-Troche; J. Aguilera-Carrera; L. Alonso-Sánchez; C. Arnaud-Carreño; L. Charúa-Guindic; E. Coss-Adame; A. de la Torre-Bravo; D. Espinosa-Medina; F. Esquivel-Ayanegui; et al. (Revista de Gastroenterología de México (English Edition), 2019)
Since the publication of the 2008 guidelines on the diagnosis and treatment of diverticular disease of the colon by the Asociación Mexicana de Gastroenterología, significant advances have been made in the knowledge of that disease. A systematic review of articles published in the medical literature from January 2008 to July 2018 was carried out to revise and update the 2008 guidelines and provide new evidence-based recommendations. All high-quality articles in Spanish and English published within that time frame were included. The final versions of the 43 statements accepted in the three rounds of voting, utilizing the Delphi method, were written, and the quality of evidence and strength of the recommendations were established for each statement, utilizing the GRADE system. The present consensus contains new data on the definition, classification, epidemiology, pathophysiology, and risk factors of diverticular disease of the colon. Special emphasis is given to the usefulness of computed tomography and colonoscopy, as well as to the endoscopic methods for controlling bleeding. Outpatient treatment of uncomplicated diverticulitis is discussed, as well as the role of rifaximin and mesalazine in the management of complicated acute diverticulitis. Both its minimally invasive alternatives and surgical options are described, stressing their indications, limitations, and contraindications. The new statements provide guidelines based on updated scientific evidence. Each statement is discussed, and its quality of evidence and the strength of the recommendation are presented. Resumen: Desde la publicación en 2008 de las guías de diagnóstico y tratamiento de la enfermedad diverticular del colon de la Asociación Mexicana de Gastroenterología ha habido avances significativos en el conocimiento de esta enfermedad. Se realizó una revisión sistemática de la literatura en PubMed de enero de 2008 a julio de 2018 con el fin de revisar y actualizar las guías 2008 y proporcionar nuevas recomendaciones basadas en la evidencia. Se incluyeron todas las publicaciones en español e inglés, de alta calidad. Se redactaron los enunciados, que fueron votados utilizando el método Delphi. Se estableció la calidad de la evidencia y la fuerza de las recomendaciones según el sistema GRADE para cada enunciado. Cuarenta y tres enunciados fueron finalmente votados y calificados. Se informan nuevos datos sobre definición, clasificación, epidemiología, fisiopatología y factores de riesgo. Se revisó con especial énfasis la utilidad de la tomografía computarizada y de la colonoscopia, así como los métodos endoscópicos para el control de la hemorragia. Se discutió sobre el tratamiento ambulatorio de la diverticulitis no complicada, el papel de la rifaximina y la mesalazina, en el manejo de la diverticulitis aguda complicada tanto en sus alternativas mínimamente invasivas hasta las opciones quirúrgicas con énfasis en sus indicaciones, limitaciones y contraindicaciones. Los nuevos enunciados proporcionan directrices basadas en la evidencia actualizada. Se presentan la discusión, el grado y la fuerza de la recomendación de cada uno de ellos. Keywords: Diverticula, Diverticulitis, Mexico, Colon, Disease, Consensus, Palabras clave: Divertículos, Diverticulitis, México, Colon, Enfermedad, Consenso